2015
DOI: 10.1089/jwh.2014.4773
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Surgical Delays in African American and White Women with Early-Stage Breast Cancer

Abstract: Background: Delays in diagnosis and treatment for breast cancer may contribute to excess deaths among African Americans. We examined racial differences in delays in diagnosis and surgical treatment for early-stage breast cancer and evaluated race-specific predictors associated with delay. Methods: A retrospective cohort study was conducted among 634 African American and white women diagnosed with invasive breast cancer between 2005 and 2010 in New Jersey. Detailed medical-chart abstraction and patient intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 39 publications
2
64
1
Order By: Relevance
“…For symptom-detected breast cancers the outcome variable for DI was >60 days vs. ≤60 days which was selected based on previously published work [28], with the outcome variable for both PI and SI being >30 days vs. ≤30 days. For screen-detected breast cancer, DI delay was defined as >30 days vs. ≤30 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For symptom-detected breast cancers the outcome variable for DI was >60 days vs. ≤60 days which was selected based on previously published work [28], with the outcome variable for both PI and SI being >30 days vs. ≤30 days. For screen-detected breast cancer, DI delay was defined as >30 days vs. ≤30 days.…”
Section: Methodsmentioning
confidence: 99%
“…While some recent studies have addressed some of the previously identified weaknesses, such as addressing the psychosocial factors that may predict risk of delay [8,28], others have focused on subgroups (such as young or low income women, early breast cancer only) [23,24,29], or have not included reasons for delay [26,30,31]. It has been suggested that the patient-related interval may be influenced by a number of factors including: “demographic factors” (such as age, education); “psychological factors” (such as fear and anxiety); “social factors” (such as work and family commitments); “behavioural factors” (such as symptom recognition, awareness and watchful waiting); and “system factors” (such as access, difficulties in making appointments, distance to medical services, coordination of diagnostic tests, and inadequate communication between and within medical services) [32].…”
Section: Introductionmentioning
confidence: 99%
“…Explanations for this phenomenon have identified later stages of cancer at the time of diagnosis (Chatterjee, He, & Keating, 2013; Silber et al, 2013) and poor access to high quality care among Black women (Curtis, Quale, Haggstrom, & Smith-Bindman, 2008; Field et al, 2011; Hunt et al, 2014) as key problems. Specifically, significantly longer time intervals have been observed between abnormal mammogram and treatment initiation for Black women as compared to White women (Ashing-Giwa et al, 2010; Bleicher et al, 2012; George et al, 2015; Gorin et al 2006). In particularly, Gorin et al, (2006) reported that Black women ages 65 years and older were 1.39 times more likely to wait more than 60 days between an abnormal mammogram and a diagnostic biopsy, and 1.64 times more likely to wait more than 30 days for treatment once breast cancer was diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…Although Black women are less likely to develop breast cancer compared with Whites, once diagnosed, Black women are less likely to receive guideline-adherent treatment [7][8][9][10] and have significantly lower 5-year survival rates [11][12][13]. These differences may be due to racial differences in tumor biology and disease aggressiveness [14][15][16], socio-economic factors and accessibility of healthcare that limit access to high quality treatment [17][18][19][20], presence of comorbid conditions [9,21,22], and psychosocial factors [23,24] that may influence responses to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in cancer treatment and treatment outcomes may partially account for the observed racial and socio-economic disparities in breast cancer mortality [2][3][4][5][6][7][8][9][10][11]. A growing number of studies indicate that African-American women are less likely to undergo breast-conserving surgery (BCS) compared with White women [2,[12][13][14] whereas other studies either reported no difference [15,16] or observed opposite findings [17,18].…”
Section: Introductionmentioning
confidence: 99%